1996
DOI: 10.1113/jphysiol.1996.sp021579
|View full text |Cite
|
Sign up to set email alerts
|

A role for synaptic and network plasticity in controlling epileptiform activity in CA1 in the kainic acid‐lesioned rat hippocampus in vitro.

Abstract: 1. Stimulation of the surviving afferents in the stratum radiatum of the CAl area in kainic acid-lesioned hippocampal slices produced graded epileptiform activity, part of which (> 20 %) involved the activation of N-methyl-D-aspartate (NMDA) receptors. There was also a failure of synaptic inhibition in this region. In this preparation, we have tested the effects of low-frequency stimulation (LFS; 1 Hz for 15 min) on synaptic responses and epileptiform activity.2. LFS resulted in long-term depression (LTD) of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Interestingly, our data demonstrate that epilepsy causes loss of mGluR LTD, but does not affect NMDA-dependent synaptic depression in the CA1 region, similar to the intact NMDAdependent LTD in the CA1 region after hippocampal lesions induced by kainic acid injection (Bernard and Wheal, 1996). These findings argue for a differential impairment of NMDAdependent and -independent forms of LTD in the CA1 region.…”
Section: Activity-dependent Modulation Of Mglur-dependent Synaptic Plsupporting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, our data demonstrate that epilepsy causes loss of mGluR LTD, but does not affect NMDA-dependent synaptic depression in the CA1 region, similar to the intact NMDAdependent LTD in the CA1 region after hippocampal lesions induced by kainic acid injection (Bernard and Wheal, 1996). These findings argue for a differential impairment of NMDAdependent and -independent forms of LTD in the CA1 region.…”
Section: Activity-dependent Modulation Of Mglur-dependent Synaptic Plsupporting
confidence: 51%
“…These findings argue for a differential impairment of NMDAdependent and -independent forms of LTD in the CA1 region. It has been suggested that the preservation of such forms of depression might be of use to decrease excitability in the epileptic hippocampus using low-frequency stimulation (Bernard and Wheal, 1996). Although we did not address this issue, it should be noted that the downregulation of mGluR5 may also have effects on NMDA-dependent forms of LTP, because mGluR5 has been implicated in NMDA-dependent LTP in the CA1 region (Lu et al, 1997;Francesconi et al, 2004).…”
Section: Activity-dependent Modulation Of Mglur-dependent Synaptic Plmentioning
confidence: 71%
“…Therefore, cell and/or synapse loss between the CA3 and CA1 regions of the hippocampus may be sufficient to prevent the hippocampal-driven control of spontaneous recurrent seizures of entorhinal origin. This view is in line with the ability of low-frequency stimulation of surviving CA1 afferents (1 Hz for 15 min) to reduce epileptiform activity in the kainic acid lesioned rat hippocampus (Bernard and Wheal, 1996). Hence, low frequency (0.25-1.5 Hz) stimulation of the hippocampal outputs in patients with temporal lobe epilepsy may represent the basis for a new direction in clinical epilepsy research.…”
Section: Acute Models With Chronic Propertiesmentioning
confidence: 59%
“…Rats were perfused with modified artificial cerebrospinal fluid and 400 m-thick slices were prepared with a Leica (Deerfield, IL) VT 1000E tissue slicer as previously described (14). Artificial cerebrospinal fluid contained (in mM) 124 NaCl, (17). Bipolar twisted NiCr wire stimulation electrodes (trimel insulated apart from 50 m at the tip) were placed in the stratum radiatum of the CA1 area close to stratum pyramidale and 0.5 mm from the recording electrode.…”
Section: Methodsmentioning
confidence: 99%